Trade potential revisited: a panel data analysis for Zimbabwe - Martínez-Galán, Enrique (2017)
We note that previous results on trade potential based on a panel data set may be biased and propose to perform these estimates with the adequate Poisson Pseudo Maximum Likelihood method, with conclusions based on confidence intervals estimated with the Delta method. This methodology is used to evaluate Zimbabwe export potential in a period characterized by strong restrictions on trade, based on the elasticity estimates generated by an augmented gravity model for six Southern African Development Community member countries and their exports to the rest of the world. For comparison purposes, we also present results with other estimation methods.